Vision and Textuality in - Birth, Monica (Revista de Filología Alemana, 2003)
This article examines the conflict between visual and textual forms of representation as a central theme of Bildung in Goethe’s Wilhelm Meisters Lehrjahre. Wilhelm’s earliest interest in the theater is clearly motivated by a desire for the exclusive vision promised by this institution. However, though Wilhelm wants a share in the illusive power of vision, he finds himself utterly seduced by security of textual representation. Through most of the novel, Wilhelm seems unable to believe his own eyes unless the validity of his vision is corroborated by some textual «evidence.» Wilhelm’s relationship to representation changes when he learns of his potential fatherhood. For the first time he recognizes the deceptive potential of textual representation and truly desires to «see» Felix as his son. Therefore, Wilhelm ends his futile pursuit of vision through the theater and joins another théa-tron — the panoptic Tower Society. Though the Tower Society will endow Wilhelm with some measure of the power of vision he so keenly desires, it comes at a cost. In submitting to the absolute ocular power of this society of visionaries, Wilhelm sacrifices his autonomy. His Bildung ends with the image of his own Bild — rendered in minute detail by the masterful and manipulative hands of the Tower Society.